2018
DOI: 10.1186/s12891-018-1977-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Total Knee Arthroplasty revision causes

Abstract: BackgroundThe number of revision Total Knee Arthroplasty (TKA) is rising in many countries. The aim of this study was the prospective assessment of the underlying causes leading to revision TKA in a tertiary care hospital and the comparison of those reasons with previously published data.MethodsIn this study patients who had revision TKA between 2010 and 2015 were prospectively included. Revision causes were categorized using all available information from patients’ records including preoperative diagnostics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
197
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(219 citation statements)
references
References 16 publications
11
197
0
11
Order By: Relevance
“…Incorrect positioning of the implant and improper mechanical axis of the lower limb can lead to accelerated implant wear and loosening, as well as suboptimal function. Aseptic loosening, instability, and malalignment were the most common reasons for late revision [52][53][54][55]. In this study, no differences were found in the value of or in the outliers of the radiographic assessment angles.…”
Section: Discussionmentioning
confidence: 47%
“…Incorrect positioning of the implant and improper mechanical axis of the lower limb can lead to accelerated implant wear and loosening, as well as suboptimal function. Aseptic loosening, instability, and malalignment were the most common reasons for late revision [52][53][54][55]. In this study, no differences were found in the value of or in the outliers of the radiographic assessment angles.…”
Section: Discussionmentioning
confidence: 47%
“…Propensity scores matching provided a method to control for selection bias between the TKA with PSI patients and TKA without PSI patients by matching the TKA with PSI patients with a subset of the TKA without PSI patient cohort has been well described in the medical literature for use in observational studies. 1,2,5,6 We included all patients' demographics, patients' clinical, and providers characteristics included in the model to calculate propensity score, and used 1:1 nearest neighbor matching of the TKA with PSI patients with TKA without PSI patients within an appropriate caliper. To examine the effectiveness of propensity score matching in balancing baseline characteristics within the matched cohorts, standardized differences (STD) were calculated for the variables included in the propensity score model.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is one of the most frequent surgical procedures and a very effective treatment option for advanced osteoarthritis of the knee, which decreases pain and improves function. 1 Because of the aging population and demands for a better quality of life, experts expect the number of TKAs to increase steadily in the next two decades. By 2030, the demand for primary total knees is projected to grow by 673% to 3.48 million procedures.…”
mentioning
confidence: 99%
“…delnden und kostenintensiven Patienten großzügig dorthin verlegt werden. Im eigenen Krankengut sind periprothetische Infektionen bereits die häufigste Revisionsursache, wobei > 90 % der Patienten in anderen Kliniken voroperiert wurden[45]. Bei frühen und akuten Infektionen mit kurzer Anamnesedauer ist der Versuch einer gelenkerhaltenden Revision mit Debridément und Wechsel der mobilen Komponenten indiziert.…”
unclassified